P089 RACIAL DISPARITIES IN HOSPITAL PRESENTATION AND OUTCOMES AFTER COLECTOMY FOR ULCERATIVE COLITIS. (7th February 2019) - McKenna, Nicholas P; Bews, Katherine A; Hanson, Kristine T; Mathis, Kellie L; Lightner, Amy L; Habermann, Elizabeth B
Abstract: Background: Up to 30% of patients with ulcerative colitis (UC) require colectomy, but whether racial disparities exist in hospital presentation, operation choice, and post-operative outcomes remains unknown. Methods: The National Inpatient Sample (NIS) was queried for all admissions between 2006-2014 with a diagnosis of UC and a procedure code for subtotal colectomy with or without an accompanying procedure code for proctectomy and ileal pouch anal anastomosis (IPAA). Univariate comparisons were performed based on race/ethnicity of non-Hispanic white, black, or Hispanic, and linear regression assessed trends in non-elective surgery over time by race. The 2005-2016 National Surgical Quality Improvement Project (NSQIP) was then queried for patients of non-Hispanic white, black, or Hispanic race/ethnicity undergoing subtotal colectomy, total proctocolectomy with or without IPAA, and completion proctectomy with IPAA for UC. To assess the impact of race on major postoperative morbidity, complications were compared between the races and a multivariable model adjusting for comorbidities and other potential risk factors was constructed. Results: The NIS query yielded 4, 310 hospitalizations with an operation (3, 800 non-Hispanic white, 214 black, 296 Hispanic). Using NIS weighting, this represents 20, 859 hospitalizations with an operation (18, 390 non-Hispanic white, 1, 036 black, 1, 432 Hispanic) in the United States over the same period. Black and Hispanic patients more often underwent non-elective surgery than non-Hispanic white patients did (black: 43%, Hispanic: 39%, non-Hispanic white: 32%; p =0.001), and this relationship persisted over the study period (Figure 1). However, neither the use of laparoscopy (black: 40%, Hispanic: 44%, non-Hispanic white: 45%; p =0.57) nor the performance of a restorative operation at the time of elective colectomy (black: 33%, Hispanic: 36%, non-Hispanic white: 32%; p =0.60) differed by race/ethnicity. Within NSQIP, 8, 953 operations were analyzed (8, 285 non-Hispanic white, 411 black, 257 Hispanic). Black and Hispanic patients experienced increased major post-operative morbidity (black: 30%, Hispanic: 31%, non-Hispanic white: 23%; p <0.001). On multivariable analysis, Hispanic ethnicity was a significant risk factor (odds ratio [OR], 1.4; 95% confidence interval [CI], 1.1-1.9) for major morbidity, while black race (OR, 1.2; 95% CI, 1.0-1.5) trended towards significance (Table I). Conclusion: Black and Hispanic patients more often underwent non-elective surgery and suffered increased postoperative morbidity compared to non-Hispanic white patients. However, racial disparities did not exist in the choice to pursue an initially restorative operation or the use of laparoscopy. An emphasis on improved outpatient UC medical management may reduce non-elective operations and postoperative morbidity in racial and ethnic minorities.